Evaluation of lipid peroxidation [TBARS] and antioxidant status for monitoring oxidative stress in students of Physical education and sport science - Mahdi, Elham Abed; Hamad, Haider Fayyadh (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The main purpose of this study was to demonstrate the impact of different exerciseson the oxidative stress in students of first class physical education and sport sciencesin Kufa university/ Iraq. Plasma enzymetic [super oxidedismutase (SOD),catalase (CAT), glutathione reductase (GSH) and glutathione peroxidase (GPX) activities ],non enzymetic [ total antioxidant capacity (TAC), uric acid (UA) and some serumtrace elements(Cu, Zn, Se)] as antioxidant ,and a marker of lipid peroxidationthiobarbituric acid –reactive substances[TBARS] were measured in( 30) students inbeginning year before they received any training or exercise programs (T0) and afterthree months (T1) then after 6 months (T2), when these students exposure for multiand variety training and games who take as lessons in first class of physical educationand sport sciences faculty which is moderate physical activities and mixed aerobicand anaerobic exercise. Our results showed increased plasma values of (SOD) ,(Cu,Zn, Se) after 3 months (T1) and 6 months (T2) when compared at baseline (T0),while plasmatic (CAT), (GPX),(GSH) were similar in three groups. On the other handa lower (TAC) levels after 3 months (T1)and 6 months (T2) when compared withlevels at base line(T0). Nevertheless, (TBARS) levels were found to be significantlyhigher in the students after 6 months when compared with levels at 3 months and atbase line levels